(untitled) (Eurasian Medical Research Periodical, 2022)
One of the tasks of modern medicine is not only treatment of malignant neoplasms (MN), but also their prevention, the possibility of early detection and prevention, which ultimately allows timely and effective treatment with preservation of patient’s quality of life. Despite the perfection of modern technologies and search of effective methods of early diagnostics, detection and determination of background diseases of larynx presents certain difficulties